Reputational risk as a factor in the offshore location choice. Issue 2 (March 2021) - Nujen, Bella B.; Solli-Sæther, Hans; Mwesiumo, Deodat; Hammer, Bianca
Abstract: Drawing on extant literature and eight case firms, this paper explores reputational risk as an essential factor in selecting offshore locations. By categorizing and aggregating insights from the empirical data and the relevant literature, the paper identifies country reputational risk as a factor determining the firm's propensity to exclude specific offshore locations. However, its effect is contingent upon managers' interpretation of the critical elements of the business environment in a particular country. Thus, the study contributes by demystifying the role of 'managerial inputs', which are often neglected within international sourcing literature. Further, reputational risk is delineated as a higher-order construct comprised of three lower-order constructs: unethical practices, institutional weakness, and quality concerns. Our findings distinguish reputational risk from the CSR framework because the dimensions of reputational risk identified in this study transcend beyond the governance, ethics, environmental and social spheres of CSR. This way, the study contributes to a holistic representation of reputational risk that can allow researchers to match its broad predictors with broad outcomes. Highlights: Delineates reputational risk to firms through case study analysis. Incorporates the lens of country-of-origin effect. Provides valuable insights on how reputational risk effects firms propensity to engage with specific locations over others. Identifies dimensions of reputational risk transcending beyond the governance, ethics, environmental and social CSR-spheres.